Process management: proposal of an analysis model - Schuch Santos, Carlos Honorato; Corrêa de Oliveira, Celmar; Prado Stradioto, Juliano; Bernardy, Rafael (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
The power of the Union, the states, and the municipalities is linked with the administrative functions delegated to these bodies. The goal of any administrative activity is the creation and maintenance of public institutions capable of meeting the population’s collective demands. To exercise this function, public bodies and institutions must be subjected to the strict and permanent control by the whole society. Administrative control of public projects execution must be effective and transparent. The aim of this paper is to propose an analytic model for the assessment and management of public projects. The development of the proposal was based upon a bibliographic-documentary research. The result identifies two types of transparency: the transparent phase and the opaque phase. This work is part of a larger study conducted to assess the degree of transparency of processes.